Multi‐triazole‐resistant Aspergillus fumigatus infections in Australia. Issue 6 (17th April 2015) - Kidd, Sarah E.; Goeman, Emma; Meis, Jacques F.; Slavin, Monica A.; Verweij, Paul E.
Summary The emergence of triazole resistance, including multi‐triazole‐resistant Aspergillus fumigatus is being reported around the world, but there has been little evidence of this problem to date in Australia. Here we describe a retrospective search of antifungal susceptibility results of all Australian clinical A. fumigatus isolates referred to the National Mycology Reference Centre, Adelaide, Australia between 2000 and 2013, yielding 13 isolates with elevated minimum inhibitory concentrations to itraconazole, posaconazole and/or voriconazole. Four isolates were found to be Aspergillus lentulus, a closely related, morphologically similar species known to have reduced susceptibility to triazoles. Analysis of the cyp51A gene of nine confirmed A. fumigatus isolates revealed two carrying the TR34/L98H mutation, one apparently locally acquired in 2004, and the other probably acquired abroad in 2012. Four isolates possessed the G54R, F46Y, Y431S and G448S mutations, respectively, whereas three isolates did not possess known cyp51A resistance mutations, raising the possibility of other, undetected resistance mechanisms. Routine antifungal susceptibility testing is definitively recommended in patients on long term and sub‐therapeutic triazole therapy with breakthrough Aspergillus infection and recommended for all clinically relevant A. fumigatus isolates.